2009
DOI: 10.1097/dad.0b013e31819f19bb
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous CD4+ Small-/Medium-Sized Pleomorphic T-Cell Lymphoma: A Cutaneous Nodular Proliferation of Pleomorphic T Lymphocytes of Undetermined Significance? A Study of 136 Cases

Abstract: Patients with skin nodules characterized by the infiltrate of pleomorphic small/medium T lymphocytes are currently classified as "primary cutaneous CD4+ small-/medium-sized pleomorphic T-cell lymphoma" (SMPTCL) or as T-cell pseudolymphoma. The distinction is often arbitrary, and patients with similar clinicopathologic features have been included in both groups. We studied 136 patients (male:female = 1:1; median age: 53 years, age range: 3-90 years) with cutaneous lesions that could be classified as small-/medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
227
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(247 citation statements)
references
References 24 publications
13
227
2
5
Order By: Relevance
“…In our case, the age at the onset of the skin lesion was 63 years and she presented with multiple, multifocal lesions. Multifocal lesions similar to our case have been less commonly described [11][12][13][14] .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our case, the age at the onset of the skin lesion was 63 years and she presented with multiple, multifocal lesions. Multifocal lesions similar to our case have been less commonly described [11][12][13][14] .…”
Section: Discussionsupporting
confidence: 61%
“…Immunohistochemically, CD3 and CD4 are positive, but CD8 and CD30 are negative in the majority of the case, and sometimes this is combined with the loss of the pan T cell markers 1,5,[11][12][13][14] . However, many studies have also reported tumors that are CD8 positive or CD4 negative 1,5,9,11,12 . In addition, many PCSM-TCL cases have shown a rich infiltrate of reactive B cells 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…small/medium T-cell lymphoma Primary cutaneous CD4? small/medium T-cell lymphoma (CD4TCL) is associated with an excellent prognosis and presents characteristically with a solitary plaque or tumor that is generally localized on the face or the upper trunk and rarely presents with multiple papules, plaques, or tumors [80,81]. Histologically, CD4TCL shows nodularto-diffuse infiltrates with a predominance of CD3?, CD4?, CD8-, CD30-small-to-medium-sized pleomorphic T cells and a small proportion (\30 %) of large CD4 pleomorphic T cells.…”
Section: Primary Cutaneous CD T-cell Lymphomamentioning
confidence: 99%
“…Often, distinguishing between primary cutaneous CD4+ small/medium-sized pleomorphic T-cell lymphoma and Tpseudolymphomas is difficult, even with TCR gene rearrangement analysis, which may be polyclonal in up to 40% of SMPTCL patients. For this reason, Beltraminelli et al suggested the name "cutaneous nodular proliferation of pleomorphic T lymphocytes of undetermined significance" for these cases 81 . In cases of a single lesion, treatment with surgical excision or radiotherapy may be performed.…”
Section: Cutaneous γ/ð T-cell Lymphomamentioning
confidence: 99%